Transposição didática de conteúdos didáticos acerca do processo de respiração celular dos vegetais presente em livros didáticos - Santos, Samantha Suyanni dos (2013)
This paper aims to discuss the rhetorical analysis of the process of didactic transposition second Chevallard (2005) about the content of cellular respiration of plants of five collections of textbooks Biology approved by the PNLD. The analyzed material corresponds to the books used in public schools and private schools and libraries that are available in the schools. Texts and images were subjected to analysis from the perspective of rhetoric Contenças (1999), Breton (2003), Reboul (2004) e Leach (2007). For analysis we checked the form of arguments and argumentative resources (such as figures of speech) used to explain the content. In the textbooks examined was possible to observe the presence of descriptive arguments, deductive, for example, authority and comparison, and how resources argumentative metonym and metaphor. The results revealed that 1) the arguments for example were employed mainly in approaches to cell and plant physiology, 2) the deductive elucidate the evolutionary aspects of the emergence and consolidation of mitochondria in plant cells, and 3) Citation of researchers characterize arguments authority that support the information in this textbook. The recurring presence of descriptive arguments characterize the textbooks as mechanistic, the content is categorized and discussed in a simplified somewhat related to other areas of knowledge making the reader as a passive recipient of information. Metaphors can aid learning content if used with the meaning of the term more known so there is no distortion in understanding what may become an epistemological obstacle. Based on this study it was possible to understand that the arguments used in the process of didactic transposition can facilitate the learning of content due to the arguments used by the authors, however, some arguments and figures of speech can interfere in a negative way.